Rethinking the Future of Indonesian Coffee: Legal, Social, and Political Perspectives - Hartati, Dwi Surya; Oktaviarni, Firya; Windarto, Windarto (Jambe Law Journal, 2023)
The idea of the Geographical Indication (IG) for coffee is not only to achieve high-quality of products but also to enhance the standard of benefits for coffee farmers. This article demonstrates discrepancies between hope and reality; quality and economic impact prevailing in the case of coffee products in Jambi Province of Indonesia. It is argued that such discrepancies potentially degrade coffee’s future in Indonesia due to farmers’ ignorance. Besides, the government policy concerning the IG has ended up with gaps between farmers’ orientation and the government’s political interest and policy in utilizing the coffee GI rights. Data were collected to analyze and address the problem from legal, social, and political perspectives. Our findings emphasize the government’s role as the grantor of rights to manage GI rights in a holistic context beyond legal positivism in order to enhance the benefits of coffee farmers in Indonesia